"Lake Gorgana" - a paleolake in the Lower Danube Valley revealed using multi-proxy and regionalisation approaches - Nowacki, Dirk; Kadereit, Annette (Quaternary international, 2019)
Geoarchaeological research at the archaeological site of Mǎgura Gorgana should elucidate the environmental setting Neolithic and Copper Age communities were faced with, when they settled along the Lower Danube Valley, Romania. This should enable a better understanding of human-environment interactions, the natural preconditions of a trading network, as well as the living conditions of the human population during this time. To reach this aim numerous corings were conducted in the study area and the sediments were analysed using a multitude of methods, as total element analyses, determination of carbon and nitrogen isotopes, radiocarbon and OSL-dating and microfaunistical analyses. The present study shows how the interpretation of the results applying a multi-proxy and a ‘regionalisation’ approach reveals the existence and the extent of ‘Lake Gorgana’, a vast paleolake that covered nearly the whole floodplain in the study area during a long phase of the Holocene and, in particular, during the settlement period at Mǎgura Gorgana in the 5th millennium BC. These new findings are of great importance for archaeological concerns but the lake sediments even more represent a valuable geoarchive containing information about e.g. changing lake ecology, paleoclimate, and the human footprint with regard to different spatial and temporal scales.
Available online 3 October 2018
Gesehen am 21.10.2019